Hubungan Lama Duduk Dengan Keluhan Nyeri Punggung Bawah Pada Dosen Institut Teknologi Sains dan Kesehatan dr.Soepraoen Malang - Dio Putra Mahardhika; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective : to understand the relationship between long sitting and complaints of low back pain in lecturers at the Institut Teknologi Sains dan Kesehatan dr. Soepraoen, Kesdam V/Brw, Malang.Methods :  This article is an analytical observational type with data collection techniques carried out by questionnaires. Collecting respondent data by sending a questionnaire using the google form submission technique with the link https://forms.gle/EWDhUAK6CsYxrYg67 to all active lecturers at the Institute of Technology, Science, and Health, dr. Soepraoen, Kesdam V/Brw, Malang, then from the results of respondents who sent data there are 47 lecturers. From these data, researchers can present it and conclude it.Results :  Sitting for or more than 7 hours has a significant relationship with complaints of low back pain in active lecturers at the  Institute of Technology, Science, and Health, dr. Soepraoen, Kesdam V/Brw, Malang.Conclusion :  Sitting duration has a significant relationship with complaints of low back pain in active lecturers at the Institute of Technology, Science, and Health, dr. Soepraoen, Kesdam V/Brw, Malang.